RESULTS OF CHEMOTHERAPY IN PATIENTS WITH MULTIDRUG-RESISTANT TUBERCULOSIS IN THE REGIONS OF THE RUSSIAN FEDERATION - V. V. Testov; S. A. Sterlikov; I. A. Vasilyeva; V. V. Erokhin; T. Ch. Kesaeva (Туберкулез и болезни лёгких)
The paper analyzes the results of treatment in 5,396 patients with multidrug-resistant tuberculosis who were treated in the regions of the Russian Federation under the Global Fund Round 4 project based on the recommended World Health Organization principles in the software management of drug-resistant tuberculosis. In the patients with multidrug-resistant tuberculosis, the total efficiency of chemotherapy was 49.6% and the efficiency of treatment in new multidrug-resistant tuberculosis cases was 59.5%. The main poor outcome of chemotherapy was its discontinuation that was 21.8%. The efficiency of chemotherapy in patients with multidrug resistant tuberculosis in the regions of the Russian Federation corresponds to that of treatment in the countries of the world and Europe.